2013
DOI: 10.1186/1471-2164-14-798
|View full text |Cite
|
Sign up to set email alerts
|

A systems biology approach using metabolomic data reveals genes and pathways interacting to modulate divergent growth in cattle

Abstract: BackgroundSystems biology enables the identification of gene networks that modulate complex traits. Comprehensive metabolomic analyses provide innovative phenotypes that are intermediate between the initiator of genetic variability, the genome, and raw phenotypes that are influenced by a large number of environmental effects. The present study combines two concepts, systems biology and metabolic analyses, in an approach without prior functional hypothesis in order to dissect genes and molecular pathways that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 76 publications
2
59
1
1
Order By: Relevance
“…A genomewide scan for selection signatures in ten cattle breeds revealed that MAP2K6 is associated with carcass weight, back fat and marbling in Korean beef cattle (Rothammer, Seichter, Förster, & Medugorac, ). Furthermore, MAP2K6 participates in the gonadotropin signalling pathway, which has been identified to be associated with divergent growth traits according to a multiomics analysis in an F 2 Charolais × Holstein population (Widmann et al., ). Regarding pigs, MAP2K6 has been associated with growth traits in the purebred Yorkshire strain (Meng et al., ) and with foot and leg structural soundness traits in domestic pigs in general (Meng et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A genomewide scan for selection signatures in ten cattle breeds revealed that MAP2K6 is associated with carcass weight, back fat and marbling in Korean beef cattle (Rothammer, Seichter, Förster, & Medugorac, ). Furthermore, MAP2K6 participates in the gonadotropin signalling pathway, which has been identified to be associated with divergent growth traits according to a multiomics analysis in an F 2 Charolais × Holstein population (Widmann et al., ). Regarding pigs, MAP2K6 has been associated with growth traits in the purebred Yorkshire strain (Meng et al., ) and with foot and leg structural soundness traits in domestic pigs in general (Meng et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Other putative candidate genes included SMAD9, which encodes a protein with a potentially important role in follicular initiation and development (Xu et al 2015), GRIK2, which encodes a protein that plays important physiological roles in maturation and puberty (Widmann et al 2013), LRBA, which encodes a protein related to reproductive traits (Taye et al 2017), H19, which encodes a protein associated with embryogenesis and fetal growth in livestock species (Zaitoun and Khatib 2006) and IGF2, which encodes a protein considered to regulate the postnatal growth and differentiation of the mammary gland (Bagnicka et al 2010). The protein encoded byLSP1 has a negative regulatory role in leukocyte recruitment to sites of inflammation and in resistance/susceptibility to intestinal nematodes (Hou et al 2012a).…”
Section: Cnvr Gene Contents and Functional Annotationsmentioning
confidence: 99%
“…Furthermore, the NCAPG gene has been shown to influence vascular smooth muscle contraction through indirect effects on arginine‐NO metabolism (Widmann et al . ). Therefore, NCAPG could influence growth through regulation of arginine metabolism.…”
Section: Association Analysis Between Snps Within the Previous Detectmentioning
confidence: 97%